Literature Review: The Influence of Family Support on the Quality of Life of Patients with Type 2 Diabetes Mellitus - Musdalipa Musdalipa; Ria Rizka Mansur (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus is a chronic, lifelong disease that requires long-term treatment, leading to a decreased quality of life. Diabetes mellitus is a condition characterized by a significant increase in blood sugar levels, or hyperglycemia, which causes a decrease in the insulin hormone. The number of people with type 2 diabetes increases annually, reaching approximately 230 million worldwide. To maintain a healthy lifestyle, patients require support from those around them, especially their families. The purpose of this study was to determine the effect of family support on the quality of life of patients with type 2 diabetes mellitus. This study used a Systems Literature Review design. Articles were collected through PubMed and Google Scholar databases using the keywords (Family Support, Type 2 Diabetes Mellitus, Quality of Life). The criteria for articles published between 2019 and 2025 were those published. The results showed that family support influences the quality of life of patients with type 2 diabetes mellitus. Conclusion: There is a significant relationship between family support and the quality of life of patients with type 2 diabetes mellitus.